1985
DOI: 10.1073/pnas.82.17.5809
|View full text |Cite
|
Sign up to set email alerts
|

Pellet microfossils: Possible evidence for metazoan life in Early Proterozoic time

Abstract: (14)(15)(16). The origin of metazoans, multicellular animals that relied on microbes as a food resource, is less well documented. The oldest proven metazoan body fossils are in the Ediacaran System (0.55-0.67 Gyr) of southeast Australia (17). The complexity and diversity of the fauna suggest that these animals had a history that extended further back than Ediacaran time. Furthermore, amino acid sequences in 02-binding proteins suggest the radiation of animals took place at or before 0.9-1 Gyr (18). Although ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Similar rocks of Archaean age (2.68 × 10 9 to 3.8 × 10 9 yr old) did not contain pellet-like microfossils. Robbins et al (1985) argued that if the Proterozoic microfossils were fossilized fecal pellets, then they provided evidence of metazoan life and a complex food web 1.9 × 10 9 yr ago, which predates macroscopic metazoan body fossils 0.67 × 10 9 yr ago, animal trace fossils 0.9 × 10 9 to 1.3 × 10 9 yr ago and fossils of unicellular eukaryotic algae 1.4 × 10 9 yr ago. Fecal pellets may have facilitated oxygenation of the ocean, leading to the Cambrian 'explosion' of multicellular life (Walter 1995, Oliwenstein 1996.…”
Section: Zooplankton Fecal Pellets In Ancient Oceansmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar rocks of Archaean age (2.68 × 10 9 to 3.8 × 10 9 yr old) did not contain pellet-like microfossils. Robbins et al (1985) argued that if the Proterozoic microfossils were fossilized fecal pellets, then they provided evidence of metazoan life and a complex food web 1.9 × 10 9 yr ago, which predates macroscopic metazoan body fossils 0.67 × 10 9 yr ago, animal trace fossils 0.9 × 10 9 to 1.3 × 10 9 yr ago and fossils of unicellular eukaryotic algae 1.4 × 10 9 yr ago. Fecal pellets may have facilitated oxygenation of the ocean, leading to the Cambrian 'explosion' of multicellular life (Walter 1995, Oliwenstein 1996.…”
Section: Zooplankton Fecal Pellets In Ancient Oceansmentioning
confidence: 99%
“…Porter & Robbins (1981) suggested that zooplankton fecal pellets contributed to the deposition of organic matter in anoxic basins, contributing to formation of the black shale deposits. Robbins et al (1985) described microfossils resembling fecal pellets of modern zooplankters in Middle Cambrian and Early Proterozoic shale. These microfossils were in rocks that also preserved sulfides analogous to modern anoxic environments that preserve fecal pellets.…”
Section: Zooplankton Fecal Pellets In Ancient Oceansmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for the existence of Metazoa on land during phase 1 is controversial (Robbins, Porter & Haberyan, 1985;Chaloner, Scott & Stephenson. 1991) and conjecture is rife.…”
Section: Terrestrial Metazoamentioning
confidence: 99%
“…Porter & Robbins 1981;Patton et al 1984;Hakes 1985;Robbins et al 1985;Sageman 1985;Cuomo & Rhoads 1987). They are most often found in dark gray to black laminated mudstones and have been attributed to planktonic organisms.…”
mentioning
confidence: 99%